Allergy on HIV Infections: A Narrative Literature Review - Muhammad Iqbal Andreas; Dwitya Elvira; Raveinal (HM Publisher, 2023)
HIV infection causes not only immune insufficiency but also immune dysregulation. Following HIV infection, cytokine profiles change, with a production of IL-4 rising along with IL-5 and a decrease in INF-g. This literature review aimed to describe allergy on HIV infection. At the initial phase after infection, cytokines produced by Th1 and Th2 are balanced, but later as the infection progresses, cytokines produced by Th2 will rise, while cytokines produced by Th1 will fall. Elevation of IL-4 will make B cells produce more IgE. Patients with even lower CD4 still have this allergic phenomenon caused by IgE. Allergic manifestations of HIV include rhinitis, asthma, adverse cutaneous drug reactions (ACDR), immune reconstitution inflammatory syndrome, hyperallergic state (IRIS), and atopic dermatitis. In conclusion, it is important to consider allergic manifestations even in AIDS patients, especially incidents of ACDR and IRIS, which can be life-threatening.